Quasi-Jensen functions - Chmieliński, Jacek (Annales Mathematicae Silesianae, 1992)
There is defined quasi-Jensen function as a solution of a certain functional inequality which generalizes the classical Jensen equation: f((x+y)/2) = (f(x)+f(y))/2. The introduced inequality is analogous to the inequality which defines J. Tabor's quasi-additive functions. The main result of this paper is to show strong relationship between quasi-Jensen and quasi-additive functions.